Congenital hepatic fibrosis (a case report) - O. O. Popovych; L. V. Moroz; Yu. V. Avdosiev; F. A. Chabanov; O. O. Voinalovych (Zaporožskij Medicinskij Žurnal)
Congenital hepatic fibrosis (CHF) is an autosomal recessive disorder of intrauterine morphogenesis of the portobiliary system, characterized by periportal fibrosis and defective remodeling of the bile ducts. The article describes the features of the clinical course, diagnosis and treatment of type I CHF in the different terms of a patient’s life: from birth to her pregnancy, during pregnancy and after childbirth.